2012
DOI: 10.1371/journal.pone.0031090
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Malaria Induces a Procoagulant and Antifibrinolytic State That Is Embryotoxic but Responsive to Anticoagulant Therapy

Abstract: Low birth weight and fetal loss are commonly attributed to malaria in endemic areas, but the cellular and molecular mechanisms that underlie these poor birth outcomes are incompletely understood. Increasing evidence suggests that dysregulated hemostasis is important in malaria pathogenesis, but its role in placental malaria (PM), characterized by intervillous sequestration of Plasmodium falciparum, proinflammatory responses, and excessive fibrin deposition is not known. To address this question, markers of coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 80 publications
(116 reference statements)
2
72
1
2
Order By: Relevance
“…3 Studies conducted in populations in Africa confirmed the association between P. falciparum submicroscopic infection during pregnancy with maternal anemia and low birth weight 57 and with a pro-coagulant/anti-fibrinolytic effect, but not with inflammation. 58 Submicroscopic infection in gestational malaria and placental malaria is a common finding in northwestern Colombia. 29 Preliminary results of ongoing studies in the region indicate an association between increased apoptosis and some pro-inflammatory cytokines during placental infection by any species (Agudelo O and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies conducted in populations in Africa confirmed the association between P. falciparum submicroscopic infection during pregnancy with maternal anemia and low birth weight 57 and with a pro-coagulant/anti-fibrinolytic effect, but not with inflammation. 58 Submicroscopic infection in gestational malaria and placental malaria is a common finding in northwestern Colombia. 29 Preliminary results of ongoing studies in the region indicate an association between increased apoptosis and some pro-inflammatory cytokines during placental infection by any species (Agudelo O and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Unstained, paraffin-embedded 5 μm mouse and human placental tissue sections (for whom the consent process and clinical and parasitological data were previously described [28]) were used for immunohistochemistry (IHC) according to previously reported methods [26] with a Polink-HRP kit for rat or rabbit antibodies (used according to manufacturer instructions; GBI, Inc. Mukilteo, WA, USA). Tissue sections were deparaffinized and rehydrated through xylene and graded alcohol series.…”
Section: Methodsmentioning
confidence: 99%
“…Like P. berghei ANKA, P. chabaudi AS -iRBCs have also been reported to accumulate in placental tissue [25]. P. chabaudi AS infection early in pregnancy leads to poor outcomes in C57BL/6J (B6) mice as well as in A/J mice, with characteristic features of human PM that lead to poor pregnancy outcomes being found in both strains [25-28]. Reduced thickness of the labyrinth, extensive hemorrhage, and coagulopathy are found in mid-gestation placentae of B6 mice infected with P. chabaudi AS during early pregnancy [26, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental malaria revealed a number of abnormalities to placental tissue such as excess of fibrinoid deposits and malarial pigment deposits (haemozoin) [8].…”
Section: Introductionmentioning
confidence: 99%